Triadic relationships between pasture exposure, gastrointestinal parasites, and hindgut microbiomes in grazing lambs - Jack Jefferson; Claire Reigate; Alessandra Giacomini; M. Jordana Rivero; Matthew Hitchings; Tamsyn Uren Webster; Konstans Wells (PLoS ONE, 2025)
Livestock grazing in confined pastures often means grazing on a less diverse diet than under more natural conditions and increased exposure to gastrointestinal parasites prevailing in these pastures. However, how sward composition influences gut microbiome (GM) diversity and its relationship with parasite burden remains poorly understood. In this study, we analysed the faecal GM of weaned lambs grazing on two distinct sward types (perennial ryegrass and a mixed-species sward) over three consecutive months using 16S rRNA sequencing, in order to assess how microbial diversity and composition are related to environmental conditions and the gastrointestinal nematode (GIN) burden in naturally infected lambs. Sward type and sampling time explained some of the variation in GM alpha diversity and community composition (beta diversity), whereas individual lamb identity accounted for considerably more variation in microbial assemblages. Shifts in the relative abundance of bacterial genera such as Saccharofermentans, Anaerosporobacter, Butyrivibrio in relation to sward type and sampling time suggest mostly adaptive fluctuations in response to diet and pasture condition. Abundance shifts of Negativibacillus, and Candidatus Saccharimonas were also associated with GIN burden, which, in turn, was higher in lambs grazing on mixed swards compared to ryegrass. Our findings add to the growing understanding of how sheep microbiomes vary with pasture management and changes in parasite burden. We highlight that individual identity may shape gut microbiota, and that potential triadic interactions among gastrointestinal parasites, sward exposure, and the gut microbiome underscore the importance of considering host, parasite, and environmental factors collectively when evaluating microbiome dynamics in grazing livestock.